The correlation of age of onset with CTG trinucleotide repeat amplification in myotonic dystrophy. Issue 11 (November 1992) - Hunter, A; Tsilfidis, C; Mettler, G; Jacob, P; Mahadevan, M; Surh, L; Korneluk, R
Abstract : The gene for myotonic dystrophy (DM) has recently been isolated and amplification of an unstable CTG trinucleotide repeat, located within the DM gene, has been identified in virtually all patients studied to date. A high proportion of DM families who are studied show a progressively earlier age of onset with succeeding generations and, in the few pedigrees reported so far, an increasing degree of amplification of the CTG repeat has been noted to parallel this trend. It has been implicit in several of the original reports on the nature of the changes in the DM gene that knowledge of CTG amplification status at the DM locus of a person will provide useful information concerning prognosis. However, no studies of genotype-phenotype correlation have been reported and there are no specific data on which to base such counsel. In this paper we report the correlation between the degree of CTG amplification and age of onset in 109 DM gene carriers from 17 families. Included are parent-child and sib-sib comparisons which provide a framework in which to incorporate DNA diagnostic studies when counselling subjects and families at risk for DM.